Chemistry and Biology of SARS-CoV-2 - Dömling, Alexander (Chem, 2020)
SARS-CoV-2 (previously 2019-nCoV or Wuhan coronavirus) caused an unprecedented fast-spreading worldwide pandemic. Although currently with a rather low mortality rate, the virus spread rapidly over the world using the modern world’s traffic highways. The coronavirus (CoV) family members were responsible for several deadly outbreaks and epidemics during the last decade. Not only governments but also the scientific community reacted promptly to the outbreak, and information is shared quickly. For example, the genetic fingerprint was shared, and the 3D structure of key proteins was rapidly solved, which can be used for the discovery of potential treatments. An overview is given on the current knowledge of the spread, disease course, and molecular biology of SARS-CoV-2. We discuss potential treatment developments in the context of recent outbreaks, drug repurposing, and development timelines.